2012
DOI: 10.1021/je3003578
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Study of (3-Ethoxypropan-1-amine + Water) Mixtures between (283.15 and 303.15) K

Abstract: Experimental densities were obtained in the binary mixtures water + 3-ethoxypropan-1-amine, for the whole composition range and at temperatures between (283.15 and 303.15) K. Derived thermodynamic properties such as apparent molar, excess molar, and excess partial molar volumes have been calculated. Limiting partial molar volumes and isobaric expansions were obtained for the two components. Different patterns of molecular aggregation and hydration schemes were detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 23 publications
4
17
0
Order By: Relevance
“…This behavior is common to other water + amphiphile mixtures 5,7,8 and is probably ascribed to the hydrophobic moiety of the amphiphile. 8 Comparing this behavior to that of aqueous mixtures of EPA 9 (presenting two fewer methylene groups in the hydrophobic moiety of the amphiphile), it is noticeable that in the water + EPA system the minimums are preceded by maximums in the very-water-rich region. This feature may be justified by the hydrolysis that occurs to a greater extent in this system as compared to that in the system in study, and as will be shown just below, it is very slight in the case of BPA.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This behavior is common to other water + amphiphile mixtures 5,7,8 and is probably ascribed to the hydrophobic moiety of the amphiphile. 8 Comparing this behavior to that of aqueous mixtures of EPA 9 (presenting two fewer methylene groups in the hydrophobic moiety of the amphiphile), it is noticeable that in the water + EPA system the minimums are preceded by maximums in the very-water-rich region. This feature may be justified by the hydrolysis that occurs to a greater extent in this system as compared to that in the system in study, and as will be shown just below, it is very slight in the case of BPA.…”
Section: Resultsmentioning
confidence: 99%
“…This procedure has often been used by us. [7][8][9]13,14 Statistical tools including F tests were used in order to optimize the number of A k (from k = 0 to 5) and B k (from k = 0 to 3) parameters to be used in each case. Experimental points at the two extreme temperatures, as examples, are shown in Figure 2, and calculated values are represented as full lines.…”
Section: Excess Molar Volumes and Isobaric Expansionsmentioning
confidence: 99%
See 3 more Smart Citations